Climatic perturbation and speciation of Southern and Eastern African Bulbul/Greenbul species (family Pycnonotidae) - Lokugalappatti, L.G. Sampath (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD (Botany and Zoology))--Stellenbosch University, 2011.